Investigating the microstructure and morphology of chips in dry, flood coolant and MQL machining of Ti-6Al-4V alloy. (23rd April 2020) - Khatri, Ashutosh; Jahan, Muhammad P.
The objective of this research is to investigate the morphology and microstructure of the chips formed during milling of Ti-6Al-4V alloy using conventional flood coolant and sustainable dry and MQL machining conditions. It was found that the chips formed in dry machining suffered a higher degree of serration indicating higher chip temperature and ineffective cooling of the chips. The bi-modal structure of Ti-6Al-4V remained the same in the bulk part of the chips. However, phase transformations were seen for all three machining conditions at the shearing plane of the chips. The chips formed in dry machining had comparatively higher percentage of β -phase due to phase transformation. For the chips obtained in flood coolant machining, the transformed β -phase possibly returned to martensitic α -phase due to rapid cooling. The MQL machined chips had the least transformation of β -phase, indicating minimal changes in mechanical properties of the machined parts in sustainable MQL machining.